Acute effect of hemodialysis on FVC, FEV1 and FEV1/FVC% in chronic kidney disease stage- V patients - Guha Roy, Upama; Begum, Shelina; Akhter Mukta, Noor E (Journal of Bangladesh Society of Physiologist, 2024)
Background: Chronic kidney disease (CKD) stage-V is associated with impairment of pulmonary functions which may be improved by taking hemodialysis treatment. Objective: To observe the acute effect of hemodialysis on FVC,FEV1 and FEV1/FVC in CKD stage-V patients. Methods: This prospective observational study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from September 2015 to August 2016 on 40 male newly diagnosedCKD stage-V patients aged 30-55years who were advised to take maintenance hemodialysis. Forty age and BMI matched apparently healthy male were control. FVC, FEV1 and FEV1/FVC%were assessed by portable digital spirometer. before and after their first hemodialysis session in patients and once in healthy control. For statistical analysis, paired and independent sample‘t’ tests were done, as applicable. Results:Percentage of predicted values of FVC and FEV1 were found significantly lower in patients than the healthy control at baseline but FEV1/FVC%was almost similar to control. Again, FVC, FEV1 and FEV1/FVC were found significantly increased after the end of hemodialysis than the before hemodialysis session. Conclusion:The pulmonary functions were reduced in newly diagnosed CKD stage-V patients and hemodialysis cause immediate improvement of lung functions in patients with CKD stage-V. J Bangladesh Soc Physiol 2022;17(2): 85-90